Síntese de 2-calcogenilbenzo[b]selenofenos derivados de 1,1- dibromoalquenos - Luz, Eduardo Quadros da (2016)
In this work, was developed a methodology for the synthesis of new 1-(2-organoylsulfanilethynyl)-2-butylselenanylbenzenes 3a-g, from 1-(2,2-dibromovinyl)-2- butylselenanylbenzenes 2a,b and thiols 4a-f, using KOH and hexane. This method has been extended to aliphatic and aromatic thiols containing electron-donating and electron-withdrawing groups and the desired products were obtained in 71-93% yields. Subsequently, when the products 3a-g were treated with I2 in CH2Cl2, they underwent electrophilic intramolecular cyclization, which led to 2-organylsulfanylbenzo[b]selenophenes 5a-g in 75-94% yields. The selenation of 1-(2,2-dibromovinyl)-2-butylselenanylbenzene 2a with diphenyl diselenides 8a-c using NaBH4/PEG-400 led it to the vinylselenides 7a-c intermediates. These were treated with KOH in hexane, forming 1-(2-organylselenanylethynyl)-2-butylselenanylbenzenes 6a-c, with 84-95% yield. Similarly, when the products 6a-c were treated with I2 in CH2Cl2, electrophilic intramolecular cyclization took place, forming the 2- organylselanylbenzo[b]selenophenes 9a-c with 82-96% yields.xiii Subsequently, 1-(2-phenylchalcogenylethynyl)-2-butylselanylbenzenes 3a and 6a have been subjected to electrophilic cyclization in the presence of other electrophiles such as Br2 and phenylselenyl bromide. In both cases the corresponding benzo[b]selenophenes 5 and 9 were obtained in good to excellent yields. Finally, in order to evaluate the reactivity of 3-iodobenzo[b]selenophene 5a, it was subjected to cross-coupling reactions catalyzed by palladium and copper salts. Initially, product 5a was tested against coupling reactions with Suzuki type Pd(OAc)2 was used as a catalyst in the presence of K3PO4 and 1,4-dioxane as solvent. Donor groups and electron withdrawals bonded to the aromatic ring were tested and good yields were obtained in all cases. Finally, Sonogashira coupling was tested, which is catalyzed by palladium and copper salts using phenylacetylene 12 as the terminal alkyne and triethylamine as the base. The desired product was obtained in 76% yield isolated after 12 hours of reaction at room temperature.